Normal Aging: Alterations in Scalp EEG Using Broadband and Band-Resolved Topographic Maps - Javed, Ehtasham; Croce, Pierpaolo; Zappasodi, Filippo; Del Gratta, Cosimo (Frontiers in Physics, 2020)
Given the majority of age-related diseases have been described as disconnection syndromes, understanding the functional connections of normal aging is of considerable importance. Here, an EEG-based scalp level analysis has been performed to identify the alterations in the synchronized brain regions in aged, compared to young persons. Two groups, aged and young subjects were studied, each consisting of 18 participants. First, conventionally extracted broadband topographic maps, also called microstate maps, were examined. The results showed an overall dominant alteration: a uniform decrease in synchronization of brain regions related to cognitive processing resources that was observed only when the maps C and D were characterized in temporal parameters. However, no remarkable change in the spatial distribution was found between the groups. This failure in identifying differences in the spatial distribution was hypothesized to be due to the presence of superimposed signals of several frequencies in the broadband signal that is used for the extraction of microstate maps. Second, spectrally resolved band-wise topographic maps, which we have shown, in a previous study, are able to detect spectral details associated with broadband microstates maps, were used to address this failure. The use of the instantaneous frequency concept is essential in the extraction of band-wise topographic maps, and represents a novelty compared to current studies. The method consists of three steps: (a) from EEG signal, the Empirical Mode Decomposition method is used to extract underlying oscillatory components; (b) these intrinsic oscillatory components are then amplitude demodulated and subjected to numerical equations for the calculation of instantaneous features, such as amplitude, and frequency; finally, (c) based on these instantaneous features, band-wise topographic maps are extracted. Here, as a first application to aging data, these band-wise topographic maps have shown the capability of capturing the age-related changes in both spatial distributions, and in temporal characterization. Spatially, the potential distribution in the aged and the young subject groups, respectively, showed differences, while, in temporal characterization, both increases and decreases were observed, suggesting the lengths of synchronized activities vary differentially, and in accordance with results from fMRI studies. These observed differences also support the dedifferentiation and compensation mechanisms.